Luminescent complexes of terbium ion for molecular recognition of ibuprofen. (27th May 2013) - Selivanova, Natalia; Vasilieva, Kristina; Galyametdinov, Yury
ABSTRACT The complexation behavior and luminescent properties of terbium (Tb3+) complexes containing bi‐dental ligands were studied: nitrogen – 1, 10‐phenanthroline, and oxygen – trifluoroacetylacetone as well as acetylacetone ligands with ibuprofen (Ibu; a non‐steroidal anti‐inflammatory drug). Aqueous and aqueous alcohol microheterogeneous solutions were used as media. The effects of solubilization by various micellar solutions, pH and ligand type on luminescent properties of Tb3+ complexes were investigated. Sensitized luminescence of mixed ligand complex Tb(1, 10‐phenanthroline)‐Ibu and dynamic quenching effect in complex Tb(trifluoroacetylacetone)3‐Ibu allow Ibu determination with the limit of detection 5.3 × 10–8 mol/L and 1.26 × 10–6 mol/L, respectively. Copyright © 2013 John Wiley & Sons, Ltd.